ANALISIS PENGARUH DEBT TO EQUITY RATIO, RETURN ON ASSET, DAN CURRENT RATIO (Studi pada Industri Manufaktur di Bursa Efek Indonesia Periode Tahun 2010-2012) - Yasin, Achmad Agus; Chabachib, M.; Haryanto, Mulyo (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2013)
This research was held to test the influence of DER, profitability, and liquidity toward DPR to increase company value. The problems in this research gap from the former research and the fenomena bussiness gap from the manufacturing company data over period 2010-2012 in the Indonesian Capital Market Directory. Therefore a deeper research to obrserve the problems which influent DPR and company value with reasonable theory is needed. The factors consist of DER, profitability, and liquidity variables.Sampling technique used is purposive sampling with criteria as manufacturing industry in IDX who provide financial report and traded during period 2009 through 2012 and forwarded to ICMD. The Data is based on publicity Indonesia Market Directory since 2009 to 2012. Obtained by amount sampel as much 15 company from 185 manufacturing industry in IDX2009-2012 period. Analysis technique used is doubled regression with smallest squareequation and hypothesis test use t-statistic to test coefficient of regression partial and also f-statistic to test the truth of collectively influence in level of significance 5%. Others also done a classic assumption test covering normality test, multicolinierity test, and heteroscedastisity test.During research period show as data research was normally distributed. Based on multicolinierity test, and heteroscedasticity test variable digressing of classic assumption has not founded, its indicate that the available data has fulfill the condition to use multi linier regression model. From the result of analyse indicate that ROA in partial significant toward DPR and DER, DPR and ROA in partial significant toward company value